CONTRASTIVE TERMINOLOGY: SEMITIC, ANGLO-GERMANIC AND LATIN CONCEPT BUILDING THROUGH COMPLEX TERMS. (AVOIDING ONE-WAY METHOD PROCEDURES IN TRANSLATION) - Aguilar-Amat, Anna; Neunzig, Willy; Sánchez-Gijón, Pilar; Touhami, Ouissem (POLISSEMA – Revista de Letras do ISCAP, 2019)
This paper aims to present a contrastive approach between three different ways of building concepts after proving the similar syntactic possibilities that coexist in terms. However, from the semantic point of view we can see that each language family has a different distribution in meaning. But the most important point we try to show is that the differences found in the psychological process when communicating concepts should guide the translator and the terminologist in the target text production and the terminology planning process. Differences between languages in the information transmission process are due to the different roles the different types of knowledge play. We distinguish here the analytic-descriptive knowledge and the analogical knowledge among others. We also state that none of them is the best when determining the correctness of a term, but there has to be adequacy criteria in the selection process. This concept building or term building success is important when looking at the linguistic map of the information society.